Pengaruh Perang Rusia-Ukraina Terhadap Kegiatan Ekspor Impor Pangan Di Kawasan Benua Eropa - Siti Alifah Handayani; Khairani Matondang; Meisha Fatma Wijaya; Riza Indriani; Tessalonika Federova Br Simanjuntak (Department of Economics Education, Universitas Sebelas Maret, 2024)
The Russian-Ukrainian invasion can resolve significant losses in terms of security, health, and even food. The invasion between the two countries has the potential to impact the food sector. This study aims to see how the analysis of the impact of the Russian-Ukrainian invasion on global food conditions pans out. To answer this research question, the author employs descriptive analysis as well as a literature review approach. Russia and Ukraine are countries that have an important role in producing food in the form of wheat, corn, and soybeans, as well as in the global food trade. But the invasions that occurred in these two countries disrupted and hampered food production, which caused global food supply chains and food trade to be hampered, causing world food price inflation. From March to May 2022, when the invasion between the two countries began, the average price of wheat, soybeans, and corn increased dramatically compared to before the COVID-19 pandemic. This invasion will hopefully be resolved through diplomacy between the two sides. In addition, all countries, including those with which they have economic cooperation relations, must be prepared to face a food crisis that is predicted to occur.